Clinical–Pathological Features and Treatment Outcome of Patients With Hobnail Variant Papillary Thyroid Carcinoma - Poma, Anello Marcello; Macerola, Elisabetta; Proietti, Agnese; Vignali, Paola; Sparavelli, Rebecca; Torregrossa, Liborio; Matrone, Antonio; Basolo, Alessio; Elisei, Rossella; Santini, Ferruccio; Ugolini, Clara (Frontiers in Endocrinology, 2022)
Papillary thyroid carcinoma (PTC) with hobnail areas above 30% is classified as hobnail variant (HVPTC). Although it is widely accepted that HVPTC has a worse outcome than classical PTC, it is unclear whether PTC with hobnail features below 30% is as aggressive as HVPTC. We gathered the largest mono-institutional series of PTC with hobnail areas and HVPTC to evaluate differences in terms of pathological features of aggressiveness, molecular profile, and treatment outcome. A total of 99 PTC with hobnail features above 5% were retrospectively selected; 34 of them met the criteria for HVPTC (0.4% of all PTC diagnosed at our institution). All tumors showed high rates of extra-thyroidal extension (40.4%), lymph node metastasis (68.1% of patients with lymphadenectomy), and vascular emboli (49.5%), with no differences according to the 30% cutoff. On the other hand, distant metastases were present in HVPTC only (9.4%). Also, advanced age, advanced disease stage, and TERT promoter mutation were associated with HVPTC. More than half of the patients with follow-up had structural or biochemical persistence after 1 year from surgery. Structural persistence was significantly more common in patients with HVPTC (37.5% vs. 8.7%), while no differences were observed considering structural and biochemical persistence together. The presence of hobnail features identifies locally aggressive tumors, and, consequently, it should be always acknowledged in the pathological report. However, tumors with more than 30% hobnail areas frequently present TERT promoter mutations, advanced disease stage, and structural persistence after radioiodine ablation.